Analyzing shifts in fertilizer use with crop rotation practices in Saskatchewan across distinct periods from 1991–94 to 2016–19 - Lika, Elisabeta; Sutherland, Chelsea; Gleim, Savannah; Smyth, Stuart J. (Frontiers in Sustainable Food Systems, 2024)
Over the last three decades, Saskatchewan, home to over 40% of Canada’s cropland, has seen transformative shifts in dryland crop production. Notably, the adoption of herbicide-tolerant canola in 1995 and the increase in nitrogen-fixing pulse crops like lentils and chickpeas have moved agricultural practices away from traditional fallow and tilled fields to more continuous crop rotations. Our study, analyzing survey data from 1991-1994 and 2016-2019, evaluates how these changes have influenced fertilizer usage, focusing on application rates, timing, and types. We anticipated that integrating nitrogen-fixing pulses and genetically modified herbicide-tolerant (GMHT) canola would promote more sustainable fertilization methods. Indeed, our results show significant reductions in nitrogen fertilizer use – by 49% to 73% in the earlier period and 3% to 19% more recently-due to the integration of these crops. GMHT canola, by reducing the dependency on synthetic nitrogen fertilizers, demonstrates a shift in fertility dynamics by enhancing nutrient uptake efficiency. This adaptation has not only reduced fertilizer costs but also contributed to more sustainable crop management. These findings highlight the environmental benefits of updated crop rotations, emphasizing the improved efficiency of fertilizer use. More broadly, they highlight the potential of expanded pulse cultivation to boost agricultural sustainability and reduce greenhouse gas emissions through better nitrogen management. While the transferability of these findings may be limited by the study’s regional focus and sample size, they hold value for informing sustainable practices in similar agricultural settings.